IMPLIKASI FILOSOFIS ONTOLOGI DAN AKSIOLOGI TERHADAP KEBIJAKAN MANAJEMEN BERKELANJUTAN - Qahfi Romula Siregar; Dedek Kurniawan Gultom; Novien Rialdy; Siti Mujiatun (JURNAL LENTERA BISNIS, 2025)
This research explores the relationship between philosophical understanding of ontology and axiology and the implementation of sustainable management policies. In the context of current environmental and social challenges, understanding the nature of organizations (intology) and ethical values ​​(axiology) is very important in formulating policies that can survive in the long term. In an effort to understand the dynamics between philosophical factors and sustainable management practices, this research uses qualitative and quantitative approaches. The research results show that an ontological understanding of natural resources is closely related to policy effectiveness, where organizations that adopt strong ethical and social values ​​tend to be more successful in implementing sustainability practices. In addition, community involvement in decision making has been proven to increase the credibility and success of policies. These findings provide practical recommendations for organizations to integrate philosophical values ​​in their training and policy development. Although this study provides valuable insights, there are limitations related to the sample size and sector focus examined, which need to be addressed in future research to gain a more comprehensive understanding of managerial sustainability.